The Effect of Triwanto Model Counseling on Tooth Brushing Knowledge of Elementary School Students Bawahan Selan 2 Banjar Regency - Rahman, Waljuni Astu; Sari, Emilda; Rahmawati, Ida; Isnawati; Habibah, Siti Sab’atul (South Eastern European Journal of Public Health, 2024)
Based on the results of a preliminary study conducted on October 23, 2023, on 10 children at State Elementary School Bawahan Selan 2, Banjar Regency, it is known that the results of 10 children have 8 children experiencing high dental caries, and of the 10 children 9 of them do not know exactly how to brush their teeth properly. This study aims to determine the effect of Triwanto model counseling on tooth brushing knowledge of students of State Elementary School Bawahan Selan 2, Banjar Regency with a total population of 110 students, the sample was taken by purposive sampling in students aged 7-9 years as many as 37 people. This research is a Quasi-Experimental research with one group pre-test and post-test design. This study used the Paired Sample test statistical test. The results of this study indicate that the average tooth brushing skills mean difference is 2.35, with ρ value = 0.000, so it is smaller than α 0.05 or (ρ = 0.000 < α 0.05), in other words, H0 is rejected and Ha is accepted. The conclusion of this study shows that there is a significant effect of Triwanto model counseling on the tooth brushing knowledge of students of State Elementary School Bawahan Selan 2, Banjar Regency. So it is expected that it is necessary to carry out continuous activities with cooperation between the school and the dental therapist of the community health centers in carrying out care service efforts at elementary schools about improving oral health brushing skills in school children.